Interactive Video: A Report from the ACE Western Regional Workshop - B. Jeanne Gleason; Scott V. Fedale; David A. King; Mary Miller (Journal of Applied Communications, 1987)
The ACE workgroup involved communicators, educators and subject specialists from a number of states and Canada.